The 2021 EULAR/American College of Rheumatology Points to Consider for Diagnosis, Management and Monitoring of the Interleukin‐1 Mediated Autoinflammatory Diseases: Cryopyrin‐Associated Periodic Syndromes, Tumour Necrosis Factor Receptor‐Associated Periodic Syndrome, Mevalonate Kinase Deficiency, and Deficiency of the Interleukin‐1 Receptor Antagonist. Issue 7 (27th May 2022) - Romano, Micol; Arici, Z. Serap; Piskin, David; Alehashemi, Sara; Aletaha, Daniel; Barron, Karyl; Benseler, Susanne; Berard, Roberta A.; Broderick, Lori; Dedeoglu, Fatma; Diebold, Michelle; Durrant, Karen; et al.
Abstract : Background: The interleukin‐1 (IL‐1) mediated systemic autoinflammatory diseases, including the cryopyrin‐ associated periodic syndromes (CAPS), tumour necrosis factor receptor‐associated periodic syndrome (TRAPS), mevalonate kinase deficiency (MKD) and deficiency of the IL‐1 receptor antagonist (DIRA), belong to a group of rare immunodysregulatory diseases that primarily present in early childhood with variable multiorgan involvement. When untreated, patients with severe clinical phenotypes have a poor prognosis, and diagnosis and management of these patients can be challenging. However, approved treatments targeting the proinflammatory cytokine IL‐1 have been life changing and have significantly improved patient outcomes. Objective: To establish evidence‐based recommendations for diagnosis, treatment and monitoring of patients with IL‐1 mediated autoinflammatory diseases to standardise their management. Methods: A multinational, multidisciplinary task force consisting of physician experts, including rheumatologists, patients or caregivers and allied healthcare professionals, was established. Evidence synthesis, including systematic literature review and expert consensus (Delphi) via surveys, was conducted. Consensus methodology was used to formulate and vote on statements to guide optimal patient care. Results: The task force devised five overarching principles, 14 statements related to diagnosis, 10 on therapy, and nine focused on long‐term monitoring that were evidence and/or consensus‐based for patients with IL‐1 mediated diseases. An outline was developed for disease‐specific monitoring of inflammation‐induced organ damage progression and reported treatments of CAPS, TRAPS, MKD and DIRA. Conclusion: The 2021 EULAR/American College of Rheumatology points to consider represent state‐of‐the‐art knowledge based on published data and expert opinion to guide diagnostic evaluation, treatment and monitoring of patients with CAPS, TRAPS, MKD and DIRA, and to standardise and improve care, quality of life and disease outcomes.